6β-hydroxygeniposide, a potent α-glucosidase inhibitor from Gardenia jasminoides growing in Viet Nam - Hoang, Vu Dinh; Hung, Nguyen Khac; Duong, Pham Quang; Thanh, Nguyen Thi Viet; Anh, Dinh Thi Phuong; Tan, Chu Van; Tuan, Cao Duc; Ngoc, Tran Hong; Bao, Truong Gia; Lam, Tran Dai (Vietnam Journal of Science and Technology, 2024)
According to the statistics of WHO in 2019, diabetes was one of the top 10 causes of death in Viet Nam and the incidence increasing day by day has required more effective treatment methods. For a long time, natural products have played an important role in drug screening programs. Gardenia jasminoides belongs to the Gardenia genus of the Rubiaceae family, in which previous research showed potential ability in diabetes treatment through various mechanisms. In this study, 3 iridoids were isolated from G. jasminoides collected in Viet Nam and the a-glucosidase inhibitory activity was evaluated for the first time. The results showed that 6b-hydroxygeniposide (2) expressed the strongest activity with IC50 at 6.38 ± 0.12 mM, while geniposide (1) and 6a-hydroxygeniposide (3) were inactive. The inhibitory mechanism of 6b- hydroxygeniposide was revealed by molecular docking and molecular dynamics. 6b- Hydroxygeniposide competed and blocked p-nitrophenyl-a-D-glucopyranoside substrate reaching the reaction center of the enzyme, which was expressed through lower non-bonding interaction energy and stable binding affinity.